2013
DOI: 10.3724/sp.j.1141.2012.05523
|View full text |Cite
|
Sign up to set email alerts
|

Progress in cathelicidins antimicrobial peptides research

Abstract: Abstract:Cathelicidins are a family of multi-functional antimicrobial peptides found in almost all types of vertebrates, where they play vital roles in the immune system. As they possess broad-spectrum antimicrobial properties, cathelicidins are not only strongly resistant to Gram-positive and Gram-negative bacteria, fungi, and viruses, but they are also active against many antibiotic-resistant clinical bacteria, adopting a special antimicrobial mechanism that is unlikely to lead to microbial resistance. Cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Furthermore, the bactericidal effect of cathelicidin family HDPs was rapid, and both chicken fowlicidins (CATH1 and 2) showed rapid killing of E. coli with the maximum killing occurring at 30 min at MIC 90 concentrations ( Xiao et al., 2006 ). More importantly, some cathelicidins have very strong activity against amounts of clinically isolated drug-resistant strains, even super drug–resistant bacteria ( Guang et al., 2012 ). Quail Cc-CATH2 and 3 displayed broad and potent antimicrobial activity against most of the 41 strains of bacteria and fungi tested, especially the clinically isolated drug-resistant strains, such as S. aureus and P. aeruginosa ( Feng et al., 2011 ).…”
Section: Perspective and Conclusionmentioning
confidence: 99%
“…Furthermore, the bactericidal effect of cathelicidin family HDPs was rapid, and both chicken fowlicidins (CATH1 and 2) showed rapid killing of E. coli with the maximum killing occurring at 30 min at MIC 90 concentrations ( Xiao et al., 2006 ). More importantly, some cathelicidins have very strong activity against amounts of clinically isolated drug-resistant strains, even super drug–resistant bacteria ( Guang et al., 2012 ). Quail Cc-CATH2 and 3 displayed broad and potent antimicrobial activity against most of the 41 strains of bacteria and fungi tested, especially the clinically isolated drug-resistant strains, such as S. aureus and P. aeruginosa ( Feng et al., 2011 ).…”
Section: Perspective and Conclusionmentioning
confidence: 99%
“…Almost every class of AMPs comprises the cathelicidin family and the defensin family, which are the two largest groups of all AMPs (17). The cathelicidin family has strong antibacterial activities (18,19), low haemolytic activity, and high cytotoxicity to drug-resistant strains (20,21).…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…PR1 and cathelicidin-PR2 had random coil configuration in sterile deionized sodium dodecyl sulfate nfiguration, as cathelicidins act by interacting with the cell membrane of pathogenic microorganisms, leading to the formation of holes in the cell membrane, leakage of cell contents, and hence killing of pathogens [22]. Not every cathelicidin has antimicrobial activity [15,23]. This study showed that the charge of cathelicidin-PR1 was +7, while the cathelicidin-PR2 net charge was 0, and the cathelicidin-PR2 no antibacterial activity.…”
Section: Circular Dichroism Analysis Of Cathelicidin-prs In Ultrapurementioning
confidence: 99%
“…Most of the cathelicidins antibacterial peptides are the α-helical structure [14]. β-sheet cathelicidins generally contain 1618 amino acids, which are folded into a hairpin structure stabilized by disulfide bonds [15].…”
Section: Introductionmentioning
confidence: 99%